Complete sequences of KPC-2-encoding plasmid p628-KPC and CTX-M-55-encoding p628-CTXM coexisted in Klebsiella pneumoniae - Wang, Li; Fang, Haihong; Feng, Jiao; Yin, Zhe; Xie, Xiaofang; Zhu, Xueming; Wang, Jie; Chen, Weijun; Yang, Ruisheng; Du, Hong; Zhou, Dongsheng (Frontiers in Microbiology, 2015)
A carbapenem-resistant Klebsiella pneumoniae strain 628 was isolated from a human case of intracranial infection in a Chinese teaching hospital. Strain 628 produces KPC-2 and CTX-M-55 encoded by two different conjugative plasmids, i.e., the IncFIIK plasmid p628-KPC and the IncI1 plasmid p628-CTXM, respectively. blaKPC-2 is captured by a Tn1721-based unit transposon with a linear structure ΔTn3-ISKpn27-blaKPC-2-ΔISKpn6-ΔTn1721, and this transposon together with a mercury resistance (mer) gene locus constitutes a 34 kb acquired drug-resistance region. blaKPC-2 has two transcription starts (nucleotides G and C located at 39 and 250 bp upstream of its coding region, respectively), which correspond to two promoters, i.e., the intrinsic P1 and the upstream ISKpn27/Tn3-provided P2 with the core -35/-10 elements TAATCC/TTACAT and TTGACA/AATAAT, respectively. blaCTX-M-55 is mobilized in an ISEcp1-blaCTX-M-55-Δorf477 transposition unit and appears to be the sole drug-resistant determinant in p628-CTXM. blaCTX-M-55 possesses a single transcription start (nucleotides G located at 116 bp upstream of its coding region), corresponding to the ISEcp1-provided P1 promoter with the core -35/-10 element TTGAAA/TACAAT. All the above detected promoters display a characteristic of constitutive expression. Coexistence of blaKPC and blaCTX-M in K. pneumoniae has been reported many times, but this is the first report to gain deep insights into genetic platforms, promoters, and expression of the two coexisted bla genes with determination of entire nucleotide sequences of the two corresponding plasmids.